2022
DOI: 10.1002/ente.202200285
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nuclear Batteries Based on Radioluminescence

Abstract: A new type of nuclear battery, based on the sandwich structure of solar cells and tritium gas‐filled radioluminescent glass tubes (RLGTs), is developed and used successfully as a low‐power source. The radioluminescence (RL) is produced by bombarding beta particles, emitted by tritium gas, on ZnS: Cu is coated on the inner cylindrical surface of a glass tube. The response of solar cells to the optical spectrum of RL is studied and corelated with the current–voltage characteristics of the nuclear battery. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…N SERS and N bulk represent the number of target molecules in the SERS sample and the normal Raman sample, respectively. According to the above equation, the corresponding EF values of sea urchin-shaped AuNCs to 4-MBA and 4-ATP were calculated to be 5.27×10 6 and 3.53×10 5 , which were comparable to other nanostructures with different shapes in previous reports [55,56]. The results suggested that different diameters of gold cores would influence the density and morphology of gold nanobranches on the surface of sea urchin-like AuNCs, which could directly affect their hot-spot distribution and plasmon resonance effect and result in an enhanced performance [31].…”
Section: Application For Sers Analysissupporting
confidence: 78%
“…N SERS and N bulk represent the number of target molecules in the SERS sample and the normal Raman sample, respectively. According to the above equation, the corresponding EF values of sea urchin-shaped AuNCs to 4-MBA and 4-ATP were calculated to be 5.27×10 6 and 3.53×10 5 , which were comparable to other nanostructures with different shapes in previous reports [55,56]. The results suggested that different diameters of gold cores would influence the density and morphology of gold nanobranches on the surface of sea urchin-like AuNCs, which could directly affect their hot-spot distribution and plasmon resonance effect and result in an enhanced performance [31].…”
Section: Application For Sers Analysissupporting
confidence: 78%